Cibercultura na experiência paisagística do turismo - Alves, Eduardo Rodrigues (2022)
This study seeks to understand elements of the tourism decentralization process in the context of cybercultural modernity, with emphasis on the mountain landscape and tourism of events.The research arises from the need to consider implications that cyberculture and the use of cyberspace infer about spatial practices, taking tourism as an important phenomenological experience with landscapes.The methodological starting point consists of a bibliographical study on important concepts for a humanistic cultural geography in order to understand tourism as part of cyberculture. In this way, concepts such as landscape and touristic landscape, phenomenological experience, geographic imaginary, tourist patrimony, informational mediation and cyberculture, among others, are explored and related. To understand the elements of tourism demand, an online questionnaire was applied on the ways of using cyberspace in everyday life and especially in tourism practices and interior of Ceará. The mechanism was built on the google forms platform and was aimed at a target audience limited to Public Institutions of Higher Education with campuses located in different regions of Ceará. Complementarily, the recognition of elements of the tourist offer in association with cyberculture took place around the tourist center of Maciço de Baturité, in particular the mountain town of Guaramiranga and the Festival Jazz e Blues Ceará. For this specific stage, the investigation was carried out based on fieldwork and the analysis of hypermedia on the internet related to the city and the festival. In view of the results obtained, the wide daily use of the internet is noted, indicating the relevance and reach of this tool in the tourist promotion process as well. There is, however, a demand for greater dissemination and provision of tourist services in cyberspace, including the promotion and accessibility to different forms of tourist patrimony (such as local and regional festivities) as a way to decentralize tourism in Ceará. Within the scope of tourist offers, we understand cyberspace as a territory, a field of disputes, in which information flows about Guaramiranga and the Festival Jazz e Blues Cear function as viable elements for the promotion of tourism and heritage. In this way, in addition to the potential, limitations and aspects that can be increased with a view to promoting regional tourism are also explored.This study seeks to understand elements of the tourism decentralization process in the context of cybercultural modernity, with emphasis on the mountain landscape and tourism of events.The research arises from the need to consider implications that cyberculture and the use of cyberspace infer about spatial practices, taking tourism as an important phenomenological experience with landscapes.The methodological starting point consists of a bibliographical study on important concepts for a humanistic cultural geography in order to understand tourism as part of cyberculture. In this way, concepts such as landscape and touristic landscape, phenomenological experience, geographic imaginary, tourist patrimony, informational mediation and cyberculture, among others, are explored and related. To understand the elements of tourism demand, an online questionnaire was applied on the ways of using cyberspace in everyday life and especially in tourism practices and interior of Ceará. The mechanism was built on the google forms platform and was aimed at a target audience limited to Public Institutions of Higher Education with campuses located in different regions of Ceará. Complementarily, the recognition of elements of the tourist offer in association with cyberculture took place around the tourist center of Maciço de Baturité, in particular the mountain town of Guaramiranga and the Festival Jazz e Blues Ceará. For this specific stage, the investigation was carried out based on fieldwork and the analysis of hypermedia on the internet related to the city and the festival. In view of the results obtained, the wide daily use of the internet is noted, indicating the relevance and reach of this tool in the tourist promotion process as well. There is, however, a demand for greater dissemination and provision of tourist services in cyberspace, including the promotion and accessibility to different forms of tourist patrimony (such as local and regional festivities) as a way to decentralize tourism in Ceará. Within the scope of tourist offers, we understand cyberspace as a territory, a field of disputes, in which information flows about Guaramiranga and the Festival Jazz e Blues Cear function as viable elements for the promotion of tourism and heritage. In this way, in addition to the potential, limitations and aspects that can be increased with a view to promoting regional tourism are also explored.